Đánh giá dịch vụ Thông tin - Thư Viện - Trương, Đại Lượng (2021)
Evaluating information library services Abstract: The article focuses on analyzing the role, levels and techniques of the evaluation of information - library services. It also hightlights the contribution of this activity to the improvement of service quality, the efficient management of resources and better library policy planning.